A view of shocks and time-scales in galactic wind-cloud models - Pinargote Morrillo, Bryan Joel (2024)
Wind-cloud models have been essential in understanding the small-scale processes occurring in galactic winds. Shocks are generated during such interactions. Some shock waves emerge in the ambient medium and some are internal to the cloud. The internal shocks can compress the gas on time-scales of the order of the so-called cloud-crushing time. This time-scale indicates how long it takes for the shock to travel across the cloud and is used to normalize the simulation times. The mathematical definition of this quantity is based on analytical considerations of the pressures involved in the wind-cloud interaction, but it often differs from the numerically-calculated time-scales. This happens particularly when non-uniform or fractal cloud geometries are considered. This thesis investigates the impact of cloud size and initial density distribution on wind-cloud systems, shock structures, and cloud disruption time-scales using 3D hydrodynamic simulations and a novel shock-tracking algorithm. We considered clouds with different sizes and density distributions with sharp and smooth edges. Using our new shock-finding routine, we were able to effectively track the internal shock cells and the most downstream dense cloud cell. Our results confirm that the Jones equation provides a better approximation compared to the Klein approximation, with a difference of only 0.33% from numerical simulations for completely spherical clouds. However, for clouds with a non-uniform density distribution, such as clouds with smooth edges, this analytical approximation does not fit properly with differences of 30.9%. Therefore, we provide a modified version of the Jones equation, which takes into account the cloud mean volume-average density and provides a better approximation to the numerically-obtained result, with a difference of only 4.59%. Overall, our study helps to understand wind-cloud interactions and provides a numerical framework to track shocks and calculate the cloud-crushing time, which can be further adapted to other cloud geometries.